VARIABILITY OF THE BIOCHEMICAL COMPOSITION OF GREEN^PODDED OF COMMON BEAN - T. K. Gorovaya; O. Yu. Sayko (Овощи России, 2015)
The results of study of 21 collection samples for variability of the biochemical composition of green beans are presented. The best selected samples characterized by stable content of total sugars, dry matter, and diet fiber are recommended for use in breeding program for development of new improved varieties of vegetable beans.